Simultaneous multislice accelerated TSE for improved spatiotemporal resolution and diagnostic accuracy in magnetic resonance neurography: a feasibility study - Preisner, Fabian; Hayes, Jennifer; Charlet, Tobias; Carinci, Flavio; Hielscher, Thomas; Schwarz, Daniel; Vollherbst, Dominik; Breckwoldt, Michael O.; Jesser, Jessica; Heiland, Sabine; Bendszus, Martin; Hilgenfeld, Tim (Investigative radiology, 2023)
Objectives - This study aims to evaluate the utility of simultaneous multislice (SMS) acceleration for routine magnetic resonance neurography (MRN) at 3 T. - Materials and Methods - Patients with multiple sclerosis underwent MRN of the sciatic nerve consisting of a standard fat-saturated T2-weighted turbo spin echo (TSE) sequence using integrated parallel acquisition technique (PAT2) acceleration and 2 T2 TSE sequences using a combination of PAT-SMS acceleration (1) to reduce scan time (PAT2-SMS2; SMS-TSEFAST) and (2) for time neutral increase of in-plane resolution (PAT1-SMS2; SMS-TSEHR). Acquisition times were 5:29 minutes for the standard T2 TSE, 3:12 minutes for the SMS-TSEFAST, and 5:24 minutes for the SMS-TSEHR. Six qualitative imaging parameters were analyzed by 2 blinded readers using a 5-point Likert scale and T2 nerve lesions were quantified, respectively. Qualitative and quantitative image parameters were compared, and both interrater and intrarater reproducibility were statistically assessed. In addition, signal-to-noise ratio/contrast-to-noise ratio (CNR) was obtained in healthy controls using the exact same imaging protocol. - Results - A total of 15 patients with MS (mean age ± standard deviation, 38.1 ± 11 years) and 10 healthy controls (mean age, 29.1 ± 7 years) were enrolled in this study. CNR analysis was highly reliable (intraclass correlation coefficient, 0.755-0.948) and revealed a significant CNR decrease for the sciatic nerve for both SMS protocols compared with standard T2 TSE (SMS-TSEFAST/SMS-TSEHR, −39%/−55%; P ≤ 0.01). Intrarater and interrater reliability of qualitative image review was good to excellent (κ: 0.672-0.971/0.617-0.883). Compared with the standard T2 TSE sequence, both SMS methods were shown to be superior in reducing pulsatile flow artifacts (P < 0.01). Ratings for muscle border sharpness, detailed muscle structures, nerve border sharpness, and nerve fascicular structure did not differ significantly between the standard T2 TSE and the SMS-TSEFAST (P > 0.05) and were significantly better for the SMS-TSEHR than for standard T2 TSE (P < 0.001). Muscle signal homogeneity was mildly inferior for both SMS-TSEFAST (P > 0.05) and SMS-TSEHR (P < 0.001). A significantly higher number of T2 nerve lesions were detected by SMS-TSEHR (P ≤ 0.01) compared with the standard T2 TSE and SMS-TSEFAST, whereas no significant difference was observed between the standard T2 TSE and SMS-TSEFAST. - Conclusions - Implementation of SMS offers either to substantially reduce acquisition time by over 40% without significantly impeding image quality compared with the standard T2 TSE or to increase in-plane resolution for a high-resolution approach and improved depiction of T2 nerve lesions while keeping acquisition times constant. This addresses the specific needs of MRN by providing different imaging approaches for 2D clinical MRN.
Gesehen am 20.06.2023